Perspectives on the Presence of Environmentally Persistent Free Radicals (EPFRs) in Ambient Particulate Matters and Their Potential Implications for Health Risk - Senlin Lu; Jiakuan Lu; Xudong Wang; Kai Xiao; Jingying Niuhe; Xinchun Liu; Shinichi Yonemochi (Atmosphere, 2025)
Environmental persistent free radicals (EPFRs) represent a class of long-lived, redox-active species with half lives spanning minutes to months. Emerging as critical environmental pollutants, EPFRs pose significant risks due to their persistence, potential for bioaccumulation, and adverse effects on ecosystems and human health. This review critically synthesizes recent advancements in understanding EPFR formation mechanisms, analytical detection methodologies, environmental distribution patterns, and toxicological impacts. While progress has been made in characterization techniques, challenges persist—particularly in overcoming limitations of electron paramagnetic resonance (EPR) spectroscopy and spin-trapping methods in complex environmental matrices. Key knowledge gaps remain, including molecular-level dynamics of EPFR formation, long-term environmental fate under varying geochemical conditions, and quantitative relationships between chronic EPFR exposure and health outcomes. Future research priorities could focus on: (1) atomic-scale mechanistic investigations using advanced computational modeling to resolve formation pathways; (2) development of next-generation detection tools to improve sensitivity and spatial resolution; and (3) integration of EPFR data into region-specific air-quality indices to enhance risk assessment and inform mitigation strategies. Addressing these gaps will advance our capacity to mitigate EPFR persistence and safeguard environmental and public health.